2020
DOI: 10.1002/mus.26820
|View full text |Cite
|
Sign up to set email alerts
|

Sonoanatomy of the deep branch of the ulnar nerve

Abstract: Introduction This study evaluated the sonoanatomy of the deep motor branch of the ulnar nerve (DBUN) using high‐resolution ultrasonography (HRUS). Methods In 60 wrists of 30 healthy adults, the gross course, cross‐sectional area (CSA), and diameter of the DBUN were observed by HRUS (frequency band 3–16 MHz). Its course was assessed by using the distance from anatomical landmarks and depth from the skin. Results The DBUN was found in all subjects with HRUS, and it branched off from the ulnar nerve before reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…They used the KCL and the line accompanying the ulnar margin of the ring finger as a reference for the access route, to avoid damage to the DBUN. Choi and Yoon 13 evaluated the DBUN in 60 wrists of 30 healthy adult patients using high-resolution ultrasonography. The course of the RMNU was evaluated using the hamate annulus and skin depth as reference.…”
Section: Discussionmentioning
confidence: 99%
“…They used the KCL and the line accompanying the ulnar margin of the ring finger as a reference for the access route, to avoid damage to the DBUN. Choi and Yoon 13 evaluated the DBUN in 60 wrists of 30 healthy adult patients using high-resolution ultrasonography. The course of the RMNU was evaluated using the hamate annulus and skin depth as reference.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study, including extremes of BMI (mean BMI of 35.2 kg/ m 2 ), had noticeably higher CSA values, supporting the hypothesis that BMI may influence the CSA value. One of the included studies compared CSA values of the ulnar nerve between subgroups based on BMI (< 25 kg/m 2 versus ≥ 25 kg/m 2 ) and found no difference at the wrist and in the hand [14]. However, included participants all had a BMI below 30.0 kg/m 2 and do not represent extremes of BMI.…”
Section: Discussionmentioning
confidence: 99%
“…CSA values of branches of the ulnar nerve (i.e. deep branch of the ulnar nerve, superficial branch of the ulnar nerve, dorsal ulnar cutaneous nerve and palmar ulnar cutaneous nerve) in the hand were described in only four studies and are shown in Table C.2 (Online Supplementary File C) [11][12][13][14].…”
Section: Branches Of the Ulnar Nerve In The Handmentioning
confidence: 99%
“…Since the shape is similar along its course, diameter may also be used rather than CSA. 17,55,56 Reported values for the DBUN are summarized in Table 1.…”
Section: Normal and Abnormal Reported Values Of The Un And Main Branchesmentioning
confidence: 99%
“…DBUN normal measurements have not been greatly reported in the literature and are based on small series of healthy individuals. Since the shape is similar along its course, diameter may also be used rather than CSA 17,55,56 …”
Section: General Considerations and Us Requisites For Un Evaluationmentioning
confidence: 99%